The effect of contact pressure on photoplethysmography - Xin Gong; Chengbo Yu; Yiguo Xuan (Institute of Advanced Engineering and Science, 2024)
In the bioinformation photoplethysmography (PPG) measurement, the precision and repeatability could be impacted by the contact pressure between the optical sensor and the measurement site. Taking the finger’s geometrical, mechanical, and optical characteristics into consideration, finite element models and Monte Carlo (MC) simulation methods were used to quantitatively analyze the effects of the deformation of different finger layers under contact pressure on its optical parameters and PPG signals during fingertip spectroscopic detection. Firstly, a 3D axisymmetric finger model was established, pelican optimization was used to find the parameter lamp that caused the simulation to best match the finger pressing behavior, modeled the deformation of each layer, and quantified the changes in their absorption and scattering coefficient. Then, before and after pressure application, photon propagation in the reflectance and transmittance modalities within the diastolic and systolic finger tissues at 660 nm and 940 nm were studied by MC simulation. The result shows that contact pressure significantly altered the thickness of the dermis and subcutaneous tissues, a decrease in tissue thickness caused an increase in optical coefficient, which resulted in a reduction in normalized pulsatile reflectance and a boost in transmittance, and the change was dependent on wavelength.